A systematic scoping review of COVID‐19 during pregnancy and childbirth. Issue 1 (17th May 2020) - Elshafeey, Farida; Magdi, Rana; Hindi, Nader; Elshebiny, Mohamed; Farrag, Nourhan; Mahdy, Shahd; Sabbour, Mohamed; Gebril, Sara; Nasser, Mohamed; Kamel, Menna; Amir, Abdelrahman; Maher Emara, Moataz; et al.
Abstract: Background: Clinical presentation and outcomes of COVID‐19 infection during pregnancy remain limited and fragmented. Objectives: To summarize the existing literature on COVID‐19 infection during pregnancy and childbirth, particularly concerning clinical presentation and outcomes. Search strategy: A systematic search of LitCovid, EBSCO MEDLINE, CENTRAL, CINAHL, Web of Science, and Scopus electronic databases. The references of relevant studies were also searched. Selection criteria: Identified titles and abstracts were screened to select original reports and cross‐checked for overlap of cases. Data collection and analysis: A descriptive summary organized by aspects of clinical presentations (symptoms, imaging, and laboratory) and outcomes (maternal and perinatal). Main results: We identified 33 studies reporting 385 pregnant women with COVID‐19 infection: 368 (95.6%) mild; 14 (3.6%) severe; and 3 (0.8%) critical. Seventeen women were admitted to intensive care, including six who were mechanically ventilated and one maternal mortality. A total of 252 women gave birth, comprising 175 (69.4%) cesarean and 77 (30.6%) vaginal births. Outcomes for 256 newborns included four RT‐PCR positive neonates, two stillbirths, and one neonatal death. Conclusion: COVID‐19 infection during pregnancy probably has a clinical presentation and severity resembling that in non‐pregnant adults. It is probably not associated with poor maternal or perinatal outcomes. Abstract : COVID‐19 infection during pregnancy probably has clinical presentation and severity similar to non‐pregnant adults and is probably not associated with poor maternal or perinatal outcomes.